ANALISIS AKUNTABILITAS PENGELOLAAN ALOKASI DANA DESA BEDANTEN KECAMATAN BUNGAH KABUPATEN GRESIK - Maulana Herlambang; Tantina Haryati (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
The amount of Village Fund Allocation (ADD) is getting bigger every year. Therefore, the village has an obligation to make financial reports on the accountability of the realization of the budget for the funds that have been used. The report is also expected to comply with the principles of accountability and transparency, in order to realizegood governance and can cause accounting to be quickly accepted and recognized. The sampling technique used was purposive sampling technique and the research data source technique was using snowball sampling technique. This type of research approach is in the form of qualitative research. Based on the results of the research, Accountability carried out by the Bedanten Village Government has been running quite well and has realized Good Governance. The Village Government has implemented the Village Fund Allocation Program in accordance with the rules and involves elements of government and accountability principles, but there is still a need to improve accountability to village communities.